Relevansi Prinsip Bagi Hasil dalam Sistem Ekonomi Islam Modern: Menyikapi Tantangan Keuangan Global - Nurdin, Fitriana; Muhammadun, Muzdalifah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This article examines the relevance of the Profit-and-Loss Sharing (PLS) principle in modern Islamic economics in response to global financial challenges and digital transformation. Employing a systematic literature review (SLR) method, the study analyzes 30 academic sources to explore: (1) the theological and ethical foundations of PLS, (2) barriers to its implementation in Islamic financial institutions, and (3) opportunities for integrating PLS with emerging technologies such as fintech and blockchain. The findings indicate that while normatively PLS promotes equitable risk-sharing and transparency, practical constraints include moral hazard, information asymmetry, and weak regulatory infrastructure. The adoption of digital finance offers potential solutions via smart contracts and Shariah-compliant platforms, contingent upon supportive and adaptive policy frameworks. This article develops a conceptual framework linking normative Islamic values with digital financial innovation, proposing a technology-driven operational model for PLS. The implications include regulatory reform, human resource development in Islamic finance, and strategic alignment with global efforts to build a more inclusive and resilient financial system.